2016
DOI: 10.1097/ccm.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Stress Ulcer Prophylaxis for Patients With Severe Sepsis*

Abstract: Since the rate of gastrointestinal bleeding requiring endoscopic hemostasis is not different comparing patients with and without stress ulcer prophylaxis, and the increase in hospital-acquired pneumonia is significant, routine stress ulcer prophylaxis for patients with severe sepsis may be unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
(29 reference statements)
3
30
1
2
Order By: Relevance
“…Moderate quality of evidence showed that prophylaxis with either H2RAs or PPIs reduced the risk of GI bleeding compared to no prophylaxis (RR 0.44; 95% CI 0.28-0.68; low quality of evidence showed a nonsignificant increase in pneumonia risk (RR 1.23; 95% CI 0.86-1.78) [538]. Recently, a large, retrospective cohort study examined the effect of stress ulcer prophylaxis in patients with sepsis and found no significant difference in the risk of C difficile infection compared to no prophylaxis [539] (ESM 13). The choice of prophylactic agent should depend on patients' characteristics, patients' values and preferences, and the local incidence of C. difficile infections and pneumonia.…”
Section: S Stress Ulcer Prophylaxismentioning
confidence: 99%
“…Moderate quality of evidence showed that prophylaxis with either H2RAs or PPIs reduced the risk of GI bleeding compared to no prophylaxis (RR 0.44; 95% CI 0.28-0.68; low quality of evidence showed a nonsignificant increase in pneumonia risk (RR 1.23; 95% CI 0.86-1.78) [538]. Recently, a large, retrospective cohort study examined the effect of stress ulcer prophylaxis in patients with sepsis and found no significant difference in the risk of C difficile infection compared to no prophylaxis [539] (ESM 13). The choice of prophylactic agent should depend on patients' characteristics, patients' values and preferences, and the local incidence of C. difficile infections and pneumonia.…”
Section: S Stress Ulcer Prophylaxismentioning
confidence: 99%
“…Moderate quality of evidence showed that prophylaxiswith either H2RAs or PPIs reduced the risk of GI bleedingcompared to no prophylaxis (RR 0.44; 95% CI 0.28-0.68; low quality of evidence showed a nonsignificant increase in pneumonia risk (RR 1.23; 95% CI 0.86-1.78) [538]. Recently, a large, retrospective cohort study examined the effect of stress ulcer prophylaxis in patients with sepsis and found nosignificant difference in the risk of C difficile infection compared to no prophylaxis [539] (ESM 13). The choice of prophylactic agent should depend on patients' characteristics, patients' values and preferences, and the local incidence of C. difficile infections and pneumonia.…”
Section: We Recommend Against Stress Ulcer Prophylaxis In Patients Wimentioning
confidence: 99%
“…Stress ulcer prophylaxis has been associated with higher VAP rates in some observational studies and in a recent meta-analysis of randomized trials [92,123,124]. A large randomized trial of pantoprazole vs placebo, however, reported no difference between arms in pneumonia rates [125].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%